Solar‐Thermally Driven Effective Molybdenum Disulfide Electrochemical Hydrogen Evolution Reactions Using Photothermal Generators. Issue 3 (12th January 2022) - Xu, Linan; Liang, Ce; Lin, Jiawen; Li, Haitao; Li, Yingli; Lin, Song; Li, Shuangwen; Feng, Lili; An, Qi
Abstract : Solar‐thermally driven functional systems have drawn extensive interest due to the environmentally benign use of sunlight. However, such function devices still suffer from the problems of preparation method, cost, and performance, therefore hindering their preparation and application. Herein, an easily prepared promising solar‐thermally powered functional system with high performance for effective sunlight‐driven hydrogen production was constructed. Such a functional system consists of a photothermal generator with a high‐performance solar absorber, together with a water‐splitting catalytic module using molybdenum disulfide loaded on carbon cloth (MoS2 ‐CC) as a cathode. The optimal gold composite polyethyleneimine‐modified graphene oxide (Au@rGO‐PEI) solar absorber coated on a commercial thermoelectricity device exhibits enhanced (45.9% higher) photothermal performance compared with rGO‐PEI; this is due to the introduction of Au nanosheets' effective plasma resonance. This as‐designed generator enables stable and long‐term output power under different ambient temperatures and sunlight. The stable hydrogen production can be achieved by combining thermoelectric units (2 in series) and electrocatalytic modules. It is envisaged that the design will promote the further development of photothermal functional devices toward use in commercial applications, help overcome problems associated with the energy crisis, and provide a practical reference for the design of solar‐driven functional devices. Abstract : Herein, an integrated functional system including a photothermal generator possessing an enhanced solar absorber and MoS2 ‐based flexible electrode for hydrogen production is developed. The critical generator fabricated by a simple spraying method enables stable and long‐term output power, even under different ambient temperatures and sunlight because of the introduction of electron donor groups and gold nanosheets' effective plasma resonance.